SU14 Morphological and immunocytochemical characterization of human-derived astrocytes from subjects with the NRG1 p.V266L genetic variant - Ugalde Araya, Karen Daniela (2019)
Background: A valine to leucine variant (p.V266L) in the transmembrane domain of neuregulin 1 (NRG1) was associated with schizophrenia in the Central Valley of Costa Rica (CVCR) population. To determine its functional significance, we are studying its biological effects in different cell types. Due to the importance of the glial cells in the Central Nervous System, we have generated astrocytes derived from induced pluripotent stem cells (iPSCs) from unaffected CVCR subjects, with and without the p.V266L variant, to explore the role of this variant in these cells. Methods: Lymphoblastoid cells lines (LCLs) from 4 unaffected subjects were transformed into iPSCs using Episomal iPSC Reprogramming Kit. Neuronal Precursor Cells were generated using AggreWell methodology and cultured in N2B27 medium complemented with 5ng/mL CTNF, 10ng/mL BMP4 and 20ng/mL FGF2 for differentiation into astrocytes. Lipofectamine transfection was used to evaluate the morphology of the astrocytes (area) and the diameter of the nucleus was measure using DAPI. Immunocytochemistry was used to measure total corrected cell fluorescence (TCCF) of GFAP, CD44, S100B, and ALDH1L1 markers. The astrocytes with the NRG1 variant had larger areas than the non-mutated ones, whereas no significant differences between both groups were found when the diameter of the nucleus was compared. The TCCF of GFAP, CD44, and S100B was higher in cells with the variant; only ALDH1L1 did not present significant differences between groups. The TCCF was measured using ImageJ and the results were analyzed using R. Results: Astrocytes with the NRG1 variant have larger areas (p<0.05), while no significant differences were found for the diameter of the nucleus (p=0.0545). The TCCF of S100B, GFAP and CD44 was higher in cells with the variant (p<0.05); only ALDH1L1 did not present significant differences (p=0.26) between groups. Discussion: Studies in animal models have shown that the presence of this variant in III NRG prevents the cleavage of the intracellular domain by the enzyme β secretase, and the extracellular domain by the enzyme γ secretase. This generates the complete reversal of the signaling pathway and an alteration in expression of genes involved in cell survival, growth and maintenance. Our cell model shows changes in the area and the expression of markers with the p.V266L variant, which might reflect both structural and metabolic alterations induced by this mutation also in astrocytes. We found larger astrocytes with larger nucleus in comparisons with studies in animal models. Our results are in agreement with previous research that show that human astrocytes are substantially larger and have more complex processes than rodent cells. Also, we show that the astrocytes in which the variant is present tend to be of a larger size. The explanation of this difference between astrocytes with and without the variant could be mediated by the differences in expression of markers used in this study. GFAP and CD44 participate in the dynamics of the cellular cytoskeleton while S100B and ALDH1L1 are involved with growth and proliferation processes. These results support a possible functional role for the p.V266L NRG1 variant in modulating astrocytic morphology and activity, and may have implications for schizophrenia. In addition, these results prove the feasibility and utility of this cell model to functionally characterize the p.V266L NRG1 variant and other genetic mutations in human astrocytes derived from EBV LCL through the iPSC technique.